Fosfluconazole for Antifungal Prophylaxis in Very Low Birth Weight Infants - Daijiro Takahashi; Tomohiko Nakamura; Reiko Shigematsu; Miyu Matsui; Shunsuke Araki; Kazuyasu Kubo; Hiroshi Sato; Akira Shirahata (International Journal of Pediatrics)
We conducted a retrospective case series study to evaluate the safety of fosfluconazole prophylaxis for preventing invasive fungal infection in VLBW infants with a central vascular access. Fosfluconazole was administered intravenously at a dose of 6 mg/kg everyday during which time a central venous catheter was placed. A total of 23 infants met the criteria for enrollment in our study. No cases of fungal infection were detected during the central venous catheter placement in the group. None of the infants had an elevated β-D-glucan, and all of them were still alive at discharge. Regarding the liver and renal function, no statistically significant differences were observed before and at the end of fosfluconazole prophylaxis. The results of this study demonstrate that fosfluconazole prophylaxis in preventing invasive fungal infection was well tolerated by VLBW infants. This is a first report to describe antifungal prophylaxis using fosfluconazole for VLBW infants.